Adaptation of Student Interpersonal Relationship Measurements: Validity and Reliability of Instruments with the Rasch Model - Nia Anggara; Nandang Rusmana; Ipah Saripah (Universitas PGRI Yogyakarta, 2026)
Interpersonal relationships are an essential foundation for identity formation, improving the quality of life, and mental wellbeing. This study aims to validate an instrument to measure the interpersonal relationships of high school and vocational school students. Survey research design, a quantitative approach, is used to provide a comprehensive understanding of interpersonal relationships. The theoretical framework for psychometric measurement is item response theory (IRT), specifically the RASCH model, using the Winstep application. The study's respondents were 351 students from 19 high schools and vocational schools across the island of Sumatra. The instrument consists of 74 statements across two aspects communication quality and participation each with 20 indicators. The results of the study showed that the interpersonal relationship was valid and reliable, meeting the criteria for item suitability, inventory dimensionality, and person and item reliability. Therefore, Guidance and Counseling Teachers can conduct more accurate assessments, detect students' various interpersonal problems early, and design interventions tailored to their needs. Keywords: validity, reliability, instrument, interpersonal relationships